The Relationship of Respectful Midwifery Care (RMC) Evaluation to Satisfaction of Midwifery Services from the Mother's Perspective in the North Jakarta Region - Heriza Syam; Hamdah Ridhaka Waljannah; Wa Ode Hajrah; Rosni Lubis; Ani Kusumastuti; Nina Primasari; Aticeh (YCAB Publisher, 2025)
Background: The labor process represents a critical phase in ensuring maternal and neonatal safety. The quality of care provided by midwives during this period plays a vital role in determining health outcomes for both mothers and newborns. To achieve optimal care, midwives are required to possess competencies in line with the standards recommended by the International Confederation of Midwives (ICM), including the implementation of Respectful Midwifery Care (RMC). The concept of RMC has also been promoted by the Indonesian Midwives Association (IBI) as an essential component of quality midwifery services. However, empirical evidence on the implementation of RMC in Indonesia remains limited. This gap highlights the need to explore women’s perspectives on the application of RMC and its association with maternal satisfaction. Objective: This study aims to assess the implementation of Respectful Midwifery Care (RMC) from the perspective of mothers receiving delivery care by midwives and to examine its relationship with maternal satisfaction in midwifery services. Methods: This research employed a quantitative approach using a cross-sectional design. The study involved 111 mothers who underwent physiological childbirth assisted by midwives at Level I Health Facilities in North Jakarta, with no maternal or neonatal complications or emergencies. Participants were selected through purposive sampling. Data were analyzed using the Chi-Square test to determine the relationship between RMC and maternal satisfaction. Results: The findings showed that 80.2% of midwives were perceived to have implemented RMC based on the mothers’ evaluations. A statistically significant association was found between the implementation of RMC and maternal satisfaction with midwifery services in North Jakarta (p = 0.000), with an Odds Ratio (OR) of 18.909. Conclusion: The implementation of Respectful Midwifery Care significantly influences maternal satisfaction with midwifery services. Mothers assisted by midwives who implement RMC are 18 times more likely to report satisfaction with their childbirth experience. The adoption of the RMC approach not only enhances maternal satisfaction but also contributes to the overall improvement of the quality of midwifery care. Keywords: respectful midwifery care; maternal satisfaction; midwifery services; quality of care